Knowledge Level of the Farmers about Hybrid Rice Cultivation in Jammu District (Indian Journal of Extension Education, 2023)
Hybrid rice technology is crucial for securing the food security of the burgeoning population of India. The study carried out in 2021 aims to assess the knowledge level of farmers regarding hybrid rice technology. Three specifically chosen sub-divisions of Jammu District; Marh, Akhnoor, and R.S. Pura, having the cultivation of hybrid rice and using the proportionate and purposive random techniques 38 from R.S. Pura, 13 from Akhnoor and 99 respondents from Marh, making a total sample size of 150 hybrid rice growers. A standardized knowledge test with reliability 0.86, was developed for assessing the knowledge level of hybrid rice growers. The Cube root method was applied to devise different knowledge categories of hybrid rice growers, which varied from medium to high. According to the results of the ANOVA test, there was no discernible difference between the knowledge levels of hybrid rice growers in the three sub-divisions.